Karakterisasi Dan Seleksi Galur F2 Hasil Persilangan Padi Lokal Merah Toraja Pare Lea X Inpari 4 (Oryza sativa L.) - Trisday Yiin Parari; Y Limbongan; Samboan Samboan (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2022)
Improvement of rice varieties in the highlands is very important considering the high effect of low temperatures on yield reduction, in addition to the production of variety quality, it needs to be considered in plant breeding activities, so that the F2 selection of red local rice crosses Toraja Pare Lea x Inpari is carried out. to select the F2 line from a cross of Pare Lea x Inpari 4 to get a superior character from the parent. The research was carried out in the rice fields of the Faculty of Agriculture, Tallunglipu District, North Toraja Regency. The research site is located at an altitude of about 750 m above sea level which was carried out from March 2019 to July 2019. This study used F1 seeds from a cross between Pare Lea x Inpari 4. This study used the Single Seed Discent (SSD) selection method. The observed characters are in the form of qualitative and quantitative characters of the results. The results showed that the diversity of characters of the F2 generation was very high, namely the average plant height of the line (115 - 150 Cm), the number of productive tillers (17 - 24), the age of harvest (120 - 145 Day), the number of pithy grain per panicle (236), weight of pithy grain per clump (126.7-143.6 g) and brown rice color (80%). Characters that had the highest positive correlation with increasing production (weight of pithy grain per clump) were the number of pithy grains per panicle (0.71), number of productive tillers (0.67), weight of 1000 seeds (0.25), and panicle length (0.24).